Robotic manipulator trajectory optimisation using an improved modified bat algorithm. (3rd July 2020) - Sahu, Pradip Kumar; Balamurali, Gunji; Biswal, Bibhuti Bhusan
This research article presents a modified bat algorithm (MBA) that provides an improved optimal solution to trajectory planning problem of industrial robot manipulators. For demonstration purpose of the trajectory optimisation problem, two robotic manipulators viz. planar 3R manipulator and 4-DOF SCARA robot manipulator has been chosen. The main objective of the proposed algorithm is to minimise Cartesian trajectory length, joint angle variation and positional error in different directions of motion. In order to achieve the above stated objective, the Cartesian length of trajectory has been selected as fitness function for the MBA and basic bat algorithm (BA) and cuckoo search (CK) algorithm. The validation of the effectiveness of the proposed MBA is performed by conducting Friedman rank test, comparing its result with the optimal solution of BA and CK for the adopted manipulators. The experimental validation of MBA results is verified with real-time simulation of a SCARA robot manipulator.